Recent Progress on Porous Carbons for Carbon Capture - Wen, Biao (Langmuir : the ACS journal of surfaces and colloids, 2024)
High emission of carbon dioxide (CO2) has caused CO2 levels to reach more than 400 ppm in air and led to a serious climate problem. In addition, in confined spaces such as submarines and aircraft, the CO2 concentration increase in the air caused by human respiration also affects human health. In order to protect the environment and human health, the search for high-performance adsorbents for carbon capture from high and low concentration gas is particularly important. Porous carbon materials, possessing the advantages of low cost and renewability, have set off a boom in the research of porous adsorbents, which have the opportunity to be utilized on a large scale for industrial carbon capture in the future. In this review, we summarize the recent research progress of porous carbons for carbon capture from flue gas and directly from air in the last five years, including activated carbon (AC), heteroatom-modified porous carbon, carbon molecular sieves (CMS), and other porous carbon materials, with a focus on the effects of temperature, water content, and gas flow rate of industrial flue gas on the performance of porous carbon adsorbents. We summarize the preparation strategies of various porous carbons and seek environmental friendly porous carbon materials preparation strategies under the premise of improving the CO2 adsorption capacity and selectivity of porous carbon adsorbents. Based on the effects of real industrial flue gas on adsorbents, we provide new ideas and evaluation methods for the development and preparation of porous carbon materials